Building material reuse: removing the roadblocks - Benjamin, Nathan (Kansas State University, 2010)
Buildings and the built environment have major resource impacts throughout their lifetimes. Much of the sustainability movement has focused on how to design, construct, and manage the built environment in ways that minimize resource impacts while enhancing the quality of built spaces. This panel will feature higher education and business professionals from Kansas with different specialties in green building. They will discuss current needs for green building in Kansas as well as ways that higher education can respond to these needs to enhance the livability, affordability, and environmental performance of the Kansas built environment.
Keywords: Reclaimed materials; Building materials; Reuse credits